Identifying key genes of classic papillary thyroid cancer in women aged more than 55 years old using bioinformatics analysis - Li, Chang-Chun; Ullah, Muhammad Hasnain Ehsan; Lin, Xiao; Shan, Su-Kang; Guo, Bei; Zheng, Ming-Hui; Wang, Yi; Li, Fuxingzi; Yuan, Ling-Qing (Frontiers in Endocrinology, 2022)
Background: The incidence rate of thyroid carcinoma markedly increased in the decades and has been likely over-diagnosed, especially papillary thyroid cancer (PTC) in females. However, the incidence of advanced-stage PTC is also rising. According to earlier studies, tumors with identical pathology might have different clinical outcomes, which implies some variances in PTC. Although the mortality of thyroid cancer has remained stable or declined, there still be an important problem in estimating whether it's benign or needs surgery for patients with PTC. Methods: After obtaining data from TCGA-THCA database by R package TCGA biolinks, 18 samples to use survival package and edgeR to make sure the difference stimulating, ClusterProfiler package to carry on GeneSet Enrichment Analysis and searched the possible pathways in Kyoto Encyclopedia of Genes and Genomes database. STRING and Cytoscape were used to construct and modify the protein-protein interaction network to get hub genes of differentially expressed genes. Next, the pROC package was used to get the ROC curves of hub genes’ disease-free survival. And then, transcription factors (TFs) and miRNAs of key genes were predicted by ENCORI and AnimalTFDB. In the end, TF-Target Genes-miRNA regulatory network was also constructed by Cytoscape. Results: Our research obtained the nine candidate genes (IFNA1, MRC1, LGALS3, LOX, POSTN, TIMP1, CD276, SDC4, TLR2). And according to ROC results, TIMP1, LOX, CD276, IFNA1, TLR2, and POSTN were considered to play a more critical role in malignant papillary thyroid cancer or immature cancer of PTC. Our analysis concludes that TIMP1, LOX, CD276, IFNA1, TLR2, and POSTN are identified as thyroid cancer biomarkers, which lead to the different clinical courses of a female older than 55 years old with papillary thyroid cancer. Especially CD276, POSTN, and IFNA1 may consider new potential biomarkers associated with PTC prognosis. Conclusions: TIMP1, LOX, CD276, IFNA1, TLR2, and POSTN are different expressions in PTCs, which lead to the various clinical courses for a female older than 55 years old with PTC. Especially CD276, POSTN, and IFNA1 may consider new potential biomarkers associated with the prognosis of thyroid cancer. And TF-Target Genes-miRNA regulatory network may help further research for PTC.